Legal Consequences of Earnings Components Management - Salma Ibrahim; Li Xu; Georgi Kalchev; Candice Linette Deal (Advances in Quantitative Analysis of Finance and Accounting, 2013)
This paper investigates how manipulating different earnings components will affect the likelihood of accounting-related shareholder litigation. Firms can manipulate earnings upward by accelerating revenue recognition, understating expenses, and overstating gains associated with special items. Firms can manipulate earnings downward by delaying revenue recognition, overstating expenses, and overstating losses associated with special items. This paper finds that firms accelerating revenue recognition or taking abnormal large losses through special items are more likely to be associated with accountingrelated shareholder litigation. Such association only exists in the post-PSLRA period.
Keywords: 330; Earnings management; Shareholder litigation; Specific Accruals